2016
DOI: 10.5489/cuaj.3684
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of active surveillance for the management of prostate cancer: A population-based analysis

Abstract: Introduction: Active surveillance (AS) is a strategy for the management of low-risk prostate cancer (PCa). However, few studies have assessed the uptake of AS at a population level and none of these were based on a Canadian population. Therefore, our objectives were to estimate the proportion of men being managed by AS in Ontario and to assess the factors associated with its uptake. Methods: This was a retrospective, population-based study using administrative databases from the province of Ontario to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Equivalent results were seen in the 75+ group to ≤75 group despite less favourable features at presentation. This imbalance of prognostic factors between age groups may relate to clinician or patient preference for an active surveillance strategy with increasing age as observed previously In a Canadian population-based study (16). We are not aware of any previous evidence of a relatively beneficial effect of hypofractionated RT in older patients with PCa.…”
Section: Discussionmentioning
confidence: 52%
“…Equivalent results were seen in the 75+ group to ≤75 group despite less favourable features at presentation. This imbalance of prognostic factors between age groups may relate to clinician or patient preference for an active surveillance strategy with increasing age as observed previously In a Canadian population-based study (16). We are not aware of any previous evidence of a relatively beneficial effect of hypofractionated RT in older patients with PCa.…”
Section: Discussionmentioning
confidence: 52%
“…Population-based studies prior to 2010 from the United States, Sweden and Canada have reported low (15%e18%) uptake of AS in eligible low-risk patients. 3,9,10 AS uptake varied from 32% to 58% between 2011e2014 in the United States 11e13 and was up to 91% in very low-risk and 74% in low-risk PC between 2011e2014 in Sweden. 14 Published studies using multi-institutional data between 2010 and 2012 demonstrated that there was a 13%e17% discontinuation of AS at 1 year, 15,16 and population-based data from Sweden found that 36% of men discontinue by 5 years.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Active surveillance (AS) has become an alternative (1)(2)(3) to definitive treatment of low/very low risk prostate cancer (PCa), focusing on prevention of overtreatment (1) and strict monitoring over time of patients to establish potential risk reclassification. However, follow-up in the majority of AS protocols is still short, and prospective validation of criteria for selecting low-risk disease is still lack-weighted (T2W), axial diffusion weighted imaging (DWI), axial dynamic contrast enhanced (DCE) and spectroscopy were performed for each patient.…”
Section: Introductionmentioning
confidence: 99%